2017
DOI: 10.1088/1361-6587/aa61e4
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear interplay of Alfvén instabilities and energetic particles in tokamaks

Abstract: The confinement of energetic particles (EP) is crucial for an efficient heating of tokamak plasmas. Plasma instabilities such as Alfvén Eigenmodes (AE) can redistribute the EP population making the plasma heating less effective, and leading to additional loads on the walls. The nonlinear dynamics of toroidicity induced AE (TAE) is investigated by means of the global gyrokinetic particle-in-cell code ORB5, within the NEMORB project. The nonperturbative nonlinear interplay of TAEs and EP due to the wave-particle… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 35 publications
2
10
0
Order By: Relevance
“…7). The TAE mode structure distortion due to the non-perturbative effects of the EPs is observed, consistent with previous simulations 3,20 and theoretical studies [22][23][24] .…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…7). The TAE mode structure distortion due to the non-perturbative effects of the EPs is observed, consistent with previous simulations 3,20 and theoretical studies [22][23][24] .…”
Section: Discussionsupporting
confidence: 91%
“…Two cases of the TAE damping are studied. In the first case, we choose m i /me = 200, since this is the parameter used in the EP driven TAE in the next section and previous ORB5 simulations 20 . In the second case, we choose m i /m e = 1836, in order to compare with the previous results where m i /m e = 1836 is used for the calculation of the TAE damping 19 .…”
Section: Toroidicity Induced Alfvén Eigenmode W/o Epsmentioning
confidence: 99%
See 1 more Smart Citation
“…The nonlinear MHD effects on the evolution of a TAE was carefully investigated, and it was found that the energy transfer from the TAE to the nonlinearly generated zonal modes with toroidal mode number n = 0 and to the higher harmonics reduces the saturation level of the TAE (Todo et al 2010. The zonal flow generation induced by AEs was first found in a gyrofluid simulation (Spong et al 1994) and was found also in gyrokinetic simulations (Zhang and Lin 2013;Biancalani et al 2016). Theory of the zonal flow generation by TAE has been also developed .…”
Section: Discussion and Summarymentioning
confidence: 99%
“…ORB5. ORB5 is a nonlinear gyrokinetic PIC code [8] with extension to electromagnetic physics and multiple species [57][58][59]. The p formulation is used and the adjustable control variate method is implemented in ORB5 [57,60], in order to avoid the 'cancellation problem'.…”
Section: Acknowledgmentsmentioning
confidence: 99%